ANALISIS KAUSALITAS STUNTING, PERTUMBUHAN EKONOMI DAN KEMISKINAN DI INDONESIA - Damayanti, Dedek Aulia; Sentosa, Sri Ulfa (Jurnal Kajian Ekonomi dan Pembangunan, 2020)
This study intends to look at the causality relationship between stunting, economic growth, and poverty in Indonesia. the type of data used is secondary data in the form of panel data from 2011 to 2018. Analysis of the data used is descriptive analysis and inductive analysis. In inductive analysis there are several tests, namely (1) Root Root Test (Unit Root Test), (2) Cointegration Test, (3) Optimum Lag Test, (4) Granger Causality Test, (5) Stability Test, (6) Impulse Response Finction Test, (7) Variance Decomposition Test. The results of this study show that: (1) There is a significant relationship exists between stunting and economic growth. (2) There is no significant relationship between economic growth and poverty. (3) there is a significant relationship between poverty and stunting in Indonesia.